Spatial variation in pollinator-mediated selection on phenology, floral display and spur length in the orchid Gymnadenia conopsea - Chapurlat, Elodie (The New phytologist, 2015)
© 2015 The Authors. New Phytologist © 2015 New Phytologist Trust.